Effect of participation of typical clinical pharmacists in patient medication in ICUs with different approaches: An investigation and case analysis - Jingwen Yin; Haiwen Shi; Changjun Li (Heliyon, 2023)
Purpose: To investigate and study the impact on patient recovery of pharmacists’ participation in the medication guidance and intervention of patients in intensive care units (ICUs). Patients and methods: We analyzed the drug use and typical cases of patients in the ICU of our hospital during clinical pharmacists' consultations or active monitoring from July 2019 to December 2020. This study included a total of 292 cases, which were distributed in the following eight areas: drug adjustment based on patients with hepatic and renal insufficiency,optimisation of treatment regimens based on drug interaction, identification and intervention based on adverse drug reactions, selection of blood purification methods based on drug intoxication, infusion access adjustment based on drug compatibility, drug adjustment based on genetic testing, antibiotic dose adjustment based on pharmacokinetics/pharmacodynamics (PK/PD) and others. The main observation indexes included consultation opinion efficiency rates and acceptance rates. The acceptance rate is calculated according to the acceptance of the clinical pharmacist's opinion by the competent doctor (fully accepted, partially accepted, not accepted). Calculate the efficiency rate according to the effect of the intervention measures. Definition of effectiveness: improvement of therapeutic effect of drugs; Avoid the occurrence of potential adverse drug reactions; Avoid the occurrence of potential drug compatibility reaction (for example, adjust the infusion sequence to avoid turbidity and sedimentation in the infusion pathway). Results: The results showed that clinical pharmacists participated in 292 cases of consultation or active monitoring of patients in the hospital's ICU based mainly on specific patient medications, drug interactions, adverse drug reactions, blood purification therapy, drug compatibility/venous infusion pathways, blood drug concentrations/drug–gene monitoring, drug PK/PD, etc. The doctor in charge acceptance rate of the consultation advice was 88.46% (completely accepted by 59.3%, partially accepted by 30.8%), and the effective rate of the consultation was 80.2%. Conclusion: Based on different purposes of intervention, the acceptance rate and efficiency rate were different. The efficiency rate with complete acceptance was significantly higher than that with partial acceptance or non-acceptance. The intervention opinions proposed by a comprehensive team in which pharmacists participate are of great help to patients and can reduce adverse reactions and medication risks. The higher the acceptance rate of their opinions, the higher the effective rate.